2022
DOI: 10.53730/ijhs.v6ns3.7309
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of women towards preeclampsia in port blair

Abstract: Preeclampsia (PE), also known as toxemia, is a multisystem disorder in pregnancy and main cause of perinatal mortality with long-term maternal complications. For a long time, PE was defined as the new onset hypertension and proteinuria after 20 weeks of gestation. This study was designed to assess the knowledge, attitude and practice of women towards preeclampsia among various urban and rural areas of Port Blair, Andaman & Nicobar Islands. A Cross – Sectional Study was conducted among 207 adult women in Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The practice of preventive measures against PE/E was notably equally divided between good and bad practice. Studies had noted that pregnant women typically take less measures to prevent PE/E[53]. The study identi ed signi cant associations between pregnant women's practices and demographic factors such as location (rural-urban divide), educational level, religion, and source of income.Multivariate analysis revealed that LGA, trimester, education level, and income source served as predictors of preventive measures practices.…”
mentioning
confidence: 99%
“…The practice of preventive measures against PE/E was notably equally divided between good and bad practice. Studies had noted that pregnant women typically take less measures to prevent PE/E[53]. The study identi ed signi cant associations between pregnant women's practices and demographic factors such as location (rural-urban divide), educational level, religion, and source of income.Multivariate analysis revealed that LGA, trimester, education level, and income source served as predictors of preventive measures practices.…”
mentioning
confidence: 99%